A Privileged and Conventional Relationship: Legal Professional Privilege and the Law Officers' Convention. - Mitchell, Rebecca; Stockdale, Michael (Modern Law Review, 2024)
Motions in the UK and Scottish Parliaments demanding the publication of legal advice to government from its Law Officers have tested the Law Officers' Convention that the existence and content of their advice is only disclosed exceptionally. They have demonstrated government relying on the Convention and legal professional privilege (LPP) to resist disclosure. This article provides the first coherent explanation of the relationship between LPP and the Convention. This is that government's right not to disclose Law Officers' advice is based on LPP with the Convention imposing a fetter on government's ability to waive privilege and/or to disclose whether Law Officers' have advised. The article provides new insights into the relationship between the UK, Scottish and Welsh Ministerial Codes and the Convention. The UK and Welsh Codes do not articulate the Convention's exception as applied in practice. The Scottish Code exhibits good practice that could be adopted elsewhere but also creates a variant Convention.